MODELING THE MARKETING COMPONENT OF THE INNOVATIVE CAPACITY OF ORGANIZATIONS ON THE BASIS OF STATISTICAL RESEARCH - Anna A. Aletdinova; Yuliya A. Makurina (Статистика и экономика, 2016)
The article considers the General scheme of the modeling process of marketing theinnovation pillar, is an attempt to summarize and systematize approaches tomodel building innovative capacity of organizations on the basis of the marketingconcept, the methods used to allocate.